Frequency, Etiology and Risk Factors of Infant Burn Injuries - Zahid, Hira; Muhammad Sharif; Janjua, Azwa; Munir, Malik Asad; Fatima, Batool; Auqil, Zahra (Indus Journal of Bioscience Research, 2024)
Background: Pediatric population in Pakistan is exposed to alarming consequences of burn injuries. Infants have a higher risk of fatality from burns than adolescents and adults. Merely few burn centers across the country are equipped with the resources and trained doctors/paramedical staff who can cater well to the neonatal and infant burn patients. We studied the frequency, etiology and risk factors of infant burn injuries to call attention and bring in public policy for its prevention and awareness among public. Methods: This was a cross-sectional study conducted in the Department of Pediatric Surgery and Pediatric Burn Unit, Mayo Hospital, Lahore, Pakistan from September 2023 to August 2024. All patients being admitted with burn injuries who were 12 months old or younger were included in the study. A structured questionnaire was filled by the duty doctor after interviewing the parents/guardians. Results: Total 2638 children presented with burns. Out of 867 admissions 75 were infants with male predominance. Mean age was 9.4+3.4 months ranging from 11 days to 12 months. 62 were scalds, 12 flame burns and one electric burn. Mothers were primary caretakers in 89% cases and 97% mothers were house wives. 71% lived in nuclear families. 64 out of 75 were kitchen accidents. All families faced major disruption in natural gas supply in their homes. Majority accidents occurred in winters and 62.6% in January and February alone. Conclusion: Infant burns can be prevented by close surveillance, keeping infants away from kitchen, support system for mothers at home and keeping stove and hot items on shelves away from reach. Provision of hot running water and infrastructure for adequate power and gas supply along with awareness/prevention campaigns by government bodies are needed to save vulnerable infants from this adversity.